ChemInform Abstract: Ligand‐Accelerated ortho‐C—H Alkylation of Arylcarboxylic Acids Using Alkyl Boron Reagents. Issue 23 (10th June 2014) - Thuy‐Boun, Peter S.; Villa, Giorgio; Dang, Devin; Richardson, Paul; Su, Shun; Yu, Jin‐Quan
Abstract A protocol for the Pd(II)‐catalyzed ortho‐C—H alkylation of phenylacetic and benzoic acids using alkylboron reagents is disclosed.